One-Step Synthesis of Conductive BNC/PPy·CuCl2 Hybrid Flexible Nanocomposites by In Situ Polymerization - Daliana Müller; Bruno N. Wesling; Gabriella M.V. Dias; Joseane C. Bernardes; Luismar M. Porto; Carlos R. Rambo; Dachamir Hotza (Advances in Materials Science and Engineering)
This work reports the one-step synthesis of bacterial nanocellulose (BNC) incorporated with polypyrrole (PPy) by chemical in situ polymerization of pyrrole (Py) using CuCl2·2H2O as both oxidant agent and functional component, varying the concentration and molar ratio. Electrical, morphological, and physical-chemical properties of these nanocomposites were investigated. The results revealed that with the increase of Py concentration and molar ratio, the nanocomposites presented traces of copper chloride and copper oxide as shown by Raman and XRD analysis. The quality of bacterial cellulose nanofibers coating by the polymer and the electrical conductivity of the nanocomposites was directly affected by those variables. The combination of the conducting polymer with the oxidant agent offers possibilities for different applications such as electronic devices and sensors.